The Relationship between Critical Thinking Skills and Quantitative Reasoning among Junior Secondary School Students in Nigeria - Awofala, Adeneye O. A.; Lawal, Ruth F (Jurnal Pendidikan Matematika, 2022)
Evidence suggests scarcity of investigations on the relationship between critical thinking (CT) and students’ achievement in quantitative reasoning (QR) in Nigeria. This correlational study adopted a quantitative model to investigate critical thinking skills as correlates of achievement in quantitative reasoning among 1500 junior secondary school students in Lagos State, Nigeria. The study involved three research questions and two valid and reliable instruments {California Critical Thinking Skills Test-Form B (CCTST with KR-20=0.88 and the Quantitative Reasoning Achievement Test (QRAT with KR-20=0.92)} were used for data collection. Data collected were analysed by deploying the statistics of mean, standard deviation, Pearson product-moment correlation coefficient, and multiple regression analysis at 5% level of significance. The outcome of the study showed a prevalent shortfall of quantitative reasoning among the junior secondary school students in Lagos State. Results showed statistically weighty associations amid critical thinking and its gauges (analysis, deductive reasoning, inductive reasoning, evaluation, and inference) with students’ quantitative reasoning achievement. In addition, the five gauges or indicators were weighty forecasters of quantitative reasoning achievement among the junior secondary school students. Based on the outcomes of this study, it was recommended that mathematics teachers should abstain from deploying teacher-centered pedagogies that are hostile to students’ comprehension of mathematical concepts and critical thinking. In conclusion, mathematics teachers should endeavour to integrate everyday life experience of the students into the mathematics taught in the classroom to enable purposeful utilization of mathematics. Bukti menunjukkan kelangkaan penyelidikan tentang hubungan antara berpikir kritis (CT) dan prestasi siswa dalam penalaran kuantitatif (QR) di Nigeria. Studi korelasional ini mengadopsi model kuantitatif untuk menyelidiki keterampilan berpikir kritis sebagai korelasi prestasi dalam penalaran kuantitatif di antara 1500 siswa sekolah menengah pertama di Lagos State, Nigeria. Penelitian ini melibatkan tiga pertanyaan penelitian dan dua instrumen yang valid dan reliabel {California Critical Thinking Skills Test-Form B (CCTST dengan KR-20=0.88 dan Quantitative Reasoning Achievement Test (QRAT dengan KR-20=0.92)} digunakan untuk pengumpulan data Data yang terkumpul dianalisis dengan menggunakan statistik mean, standar deviasi, koefisien korelasi product-moment Pearson, dan analisis regresi berganda pada tingkat signifikansi 5%.Hasil penelitian menunjukkan kekurangan penalaran kuantitatif yang lazim di antara sekolah menengah pertama siswa di Negara Bagian Lagos Hasil menunjukkan asosiasi yang berbobot secara statistik di antara berpikir kritis dan pengukurnya (analisis, penalaran deduktif, penalaran induktif, evaluasi, dan inferensi) dengan pencapaian penalaran kuantitatif siswa. prestasi penalaran siswa SMP Berdasarkan hasil penelitian ini, Direkomendasikan bahwa guru matematika harus menjauhkan diri dari menyebarkan pedagogi yang berpusat pada guru yang memusuhi pemahaman siswa tentang konsep matematika dan pemikiran kritis. Kesimpulannya, guru matematika harus berusaha untuk mengintegrasikan pengalaman hidup sehari-hari siswa ke dalam matematika yang diajarkan di kelas untuk memungkinkan pemanfaatan matematika yang bertujuan.